HEG1 indicates poor prognosis and promotes hepatocellular carcinoma invasion, metastasis, and EMT by activating Wnt/β-catenin signaling. (25th July 2019) - Zhao, Yan-rong; Wang, Ji-long; Xu, Cong; Li, Yi-ming; Sun, Bo; Yang, Lian-yue
Abstract : Heart development protein with EGF-like domains 1 (HEG1) plays critical roles in embryo development and angiogenesis, which are closely related to tumor progression. However, the role of HEG1 in hepatocellular carcinoma (HCC) remains unknown. In the present study, we explored the clinical significance, biological function and regulatory mechanisms of HEG1 in HCC and found that HEG1 is significantly up-regulated in HCC cell lines and primary tumor samples. Additionally, high HEG1 expression is correlated with aggressive clinicopathological features. Patients with high HEG1 expression had shorter overall survival (OS) and disease-free survival (DFS) than those with low HEG1 expression, which indicated that HEG1 is an independent factor for poor prognosis. Lentivirus-mediated HEG1 overexpression significantly promotes HCC cell migration, invasion and epithelial–mesenchymal transition (EMT) in vitro and promotes intrahepatic metastasis, lung metastasis and EMT in vivo . Opposing results are observed when HEG1 is silenced. Mechanistically, HEG1 promotes β-catenin expression and maintains its stability, leading to intracellular β-catenin accumulation, β-catenin nuclear translocation and Wnt signaling activation. Loss- and gain-of-function assays further confirmed that β-catenin is essential for HEG1-mediated promotion of HCC invasion, metastasis and EMT. In conclusion, HEG1 indicates poor prognosis; plays important roles in HCC invasion, metastasis and EMT by activating Wnt/β-catenin signaling; and can serve as a potentially valuable prognostic biomarker and therapeutic target for HCC.